Characterization of Fruit Development, Antioxidant Capacity, and Potential Vasoprotective Action of Peumo (Cryptocarya alba), a Native Fruit of Chile - Mónika Valdenegro; Maricarmen Bernales; Marcela Knox; Raúl Vinet; Eduardo Caballero; Aníbal Ayala-Raso; Denisa Kučerová; Rohitesh Kumar; Jitka Viktorová; Tomáš Ruml; Carlos R. Figueroa; Lida Fuentes (MDPI AG, 2021)
The peumo (Cryptocarya alba) is a native fruit from central Chile that belongs to the Lauraceae family. To characterize the development and the potential health benefits of this edible fruit, quality and physiological parameters, along with antioxidant capacity, were evaluated during three clearly defined developmental stages of the fruit in two seasons. The most distinguishable attributes of ripe fruit were the change in size and color. Low CO2 production and no detectable ethylene levels suggested non-climacteric behavior of the peumo fruit. Peumo demonstrate a significant increase in their antioxidant capacity per 1 g of fresh weight (FW) of the sample, from small to ripe fruit. Higher values in ripe fruit (FRAP: 37.1-38.3 µmol FeSO4/gFW, TEAC: 7.9-8.1 mmol TE/gFW, DPPH: 8.4-8.7 IC50 μg/mL, and ORAC: = 0.19-0.20 mmol TE/gFW) were observed than those in blueberry fruit (FRAP: 4.95 µmol FeSO4/gFW, TEAC: 1.25 mmol TE/gFW, DPPH: 11.3 IC50 μg/mL, and ORAC: 0.032 mmol TE/ gFW). The methanol extracts of ripe fruit displayed the presence of polyphenol acids and quercetin, an ORAC value of 0.637 ± 0.061 mmol TE per g dried weight (DW), and a high cellular antioxidant and anti-inflammatory potential, the latter exceeding the effect of quercetin and indomethacin used as standard molecules. Also, the assay of isolated rat aorta with endothelium-dependent relaxation damage demonstrated that the peumo extract induced vascular protection, depending on its concentration under a high glucose condition. These results demonstrate that these endemic fruits have a good chance as ingredients or foods with functional properties.